How WEIRD and Androcentric Is Sex Research? Global Inequities in Study Populations. Issue 7 (2nd September 2022) - Klein, Verena; Savaş, Özge; Conley, Terri D.
ABSTRACT: Previous researchers have noted the domination of Western, Educated, Industrialized, Rich, and Democratic (WEIRD) samples in fields like psychology. In this study we asked: how WEIRD and androcentric is contemporary sex research? We focused on two historically underrepresented groups in research, namely non-WEIRD and women/gender non-conforming samples. We analyzed 2, 223 articles drawn from five leading journals in scientific sexuality research ( Archives of Sexual Behavior, Journal of Sex Research, Journal of Sex and Marital Therapy, Journal of Sexual Medicine, and International Journal of Sexual Health ). We coded the national context and gender of sampled populations for articles published between 2015 and 2019 in these journals. Results indicated that WEIRD populations dominate the published findings in sex research (ranging from 68% to 88%). Two journals had a higher number of studies that only included men as participants, and one a higher number of samples that consisted of only women, and very few included gender diverse samples (i.e., non-binary, trans*, intersex). Recommendations for improving the current research and publishing practices are discussed.